Synthesis, characterization and cell response of silicon/gallium co-substituted tricalcium phosphate bioceramics - He, Fupo; Qiu, Chao; Wang, Yao; Lu, Teliang; Ye, Jiandong (Journal of materials science, 2022)
The aim of this study was to fabricate silicon/gallium co-substituted tricalcium phosphate bioceramics having the ability to promote osteoblast activities as well as hinder osteoclast activities. The silicon/gallium co-substituted tricalcium phosphates were synthesized with a solid-state reaction route, and their bioceramics were prepared by the process of molding and sintering. The bioceramics were characterized employing X-ray fluorescence spectroscopy, X-ray diffraction and scanning electron microscopy. Porosity and compressive strength tests, and experiments for in vitro cell response evaluation were performed. The results manifested that silicon/gallium co-substitution promoted transition of β-tricalcium phosphate to α-tricalcium phosphate and additionally gave rise to new phases of silicocarnotite and Ca 2 SiO 4 . In contrast to a single gallium substitution, the silicon/gallium co-substitution retarded the densification process but retained the high mechanical strength of bioceramics, and maintained the inhibitory effect of gallium on the osteoclast activities. The tricalcium phosphate bioceramics with substitutions of 2.5 mol% gallium and 10 mol% silicon possessed considerable mechanical strength, enhanced osteoblast activities and restrained osteoclast activities, so they were expected to efficiently reconstruct the bone defects in the environment of osteoporosis.